2001
DOI: 10.5194/npg-8-181-2001
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear saturation of Rayleigh-Taylor instability and generation of shear flow in equatorial spread-F plasma

Abstract: Abstract. An analysis of low order mode coupling equations is used to describe the nonlinear behavior of the RayleighTaylor (RT) instability in the equatorial ionosphere. The nonlinear evolution of RT instability leads to the development of shear flow. It is found that there is an interplay between the nonlinearity and the shear flow which compete with each other and saturate the RT mode, both in the collisionless and collisional regime. However, the nonlinearly saturated state, normally known as vortices or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The issue of shear flow stabilization remains contentious, and a number of recent theoretical and computational studies continue to support the idea (Hassam, 1992;Sekar and Kelley, 1998;Chakrabarti and Lakhina, 2003). Chakrabarti and Lakhina (2001) further showed that the nonlinear evolution of the Rayleigh-Taylor instability itself induces shear flow which contributes to the saturation of the instability.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of shear flow stabilization remains contentious, and a number of recent theoretical and computational studies continue to support the idea (Hassam, 1992;Sekar and Kelley, 1998;Chakrabarti and Lakhina, 2003). Chakrabarti and Lakhina (2001) further showed that the nonlinear evolution of the Rayleigh-Taylor instability itself induces shear flow which contributes to the saturation of the instability.…”
Section: Discussionmentioning
confidence: 99%
“…where the various symbols have their usual meaning (Huba et al, 1985;Chakrabarti and Lakhina, 2001). Solving electron momentum Eq.…”
Section: Model Basic Equations and Equilibriummentioning
confidence: 99%
“…equatorial Spread-F and ionospheric plasma clouds). It is also known that the RT mode may self-consistently generate a velocity shear which can then stabilize the mode (Finn et al, 1992;Chakrabarti and Lakhina, 2001).…”
Section: Introductionmentioning
confidence: 99%